“A hora e vez de Augusto Matraga” e “Duelo”. Um estudo semiótico de contos de Sagarana - Couto, Roseli Cantalogo (2008)
This dissertation analyses the tales “A hora e vez de Augusto Matraga” and “Duelo”, by João Guimarães Rosa and uses as theoretical reference the French Semiotics. The objective is to describe the construction of the meaning of these tales, focusing aspects of their pragmatic, figurative, passional and enunciative dimensions. It is particularly centered on the actors who manifest their pragmatic, cognitive, and passional course. In the pragmatic and cognitive course, the transformations of state the actors experience were described and, in the passional course, their state of the soul, observing the passions that move them. It was noticed that the vengeance passion manifest itself in both tales, creating effects of various meanings. The French semiotics theory presuppositions were used based on the Dicionário de Semiótica by A. J. Greimas and J. Courtés, on the work of Denis Bertrand, Caminhos da Semiótica Literária, and on Patrizia Lombardo’s work, who in her Dictionnaire des Passions Littéraires devotes and entry to the study of revenge. We also based this paper on the works of semiotics in Brazil by Diana Luz Pessoa de Barros and José Luíz Fiorin. Critical studies on Sagarana were used as foundation to assist in the understanding of the Rosian universe, focusing especially in the work of scholars who deal with the tales of this analysis. Keywords: Guimarães Rosa, semiotics, actor, course, passion, revenge